(untitled) (Bangladesh Pharmaceutical Journal, 2018)
Hypertension is a major challenge in human immunodeficiency virus (HIV) infected people globally. A prospective, cross-sectional study comprising two hundred and eighteen HIV-infected patients was conducted in Antiretroviral Therapy Clinic of General Hospital, Offa between November 2015 and December, 2016. Patients’ blood pressure was evaluated using Omron automated blood pressure monitor following standard procedures. Dual weight and height balance was utilized to measure the weight and height of the subjects. Hypertension incidence among patients receiving combined antiretroviral therapy (cART) was 34%, while those that were yet to start cART was 9.6 %. In HIVinfected women on cART, occurrence of hypertension was high (75.5%) as compared to men (24.5%). The hypertension pervasiveness in HIV-infected patients on cART was 75.5% in women and 24.5% in men. Risk factors that were markedly linked with hypertension among patients on cART include body mass index (OR: 3.29,95% CI:1.21-2.27; p< 0.050), sedentary lifestyle (OR: 1.63, 95% CI:1.20-5.38; p < 0.043), age (OR: 2.17, 95% CI: 1.22-2.33; p< 0.004) and gender (OR: 1.63, 95% CI: 0.85-2.41; p < 0.037). Patients on cART were found to have higher hypertension prevalence than cART-naive. The cART, however, is not a risk factor for hypertension. Bangladesh Pharmaceutical Journal 21(1): 35-41, 2018